Comparison of lipid levels in the diabetic and non diabetic patients: a study in a tertiary care hospital - Veeramalla, Vydehi; Madas, Swetha (International Journal of Advances in Medicine, 2017)
Background: The incidence of coronary artery diseases is 3 to 5 times higher in both male and female diabetic patients compared to general population. Individuals with diabetes may have several forms of dyslipidemia leading to additive cardiovascular risk of hyperglycemia. This study was therefore conducted to identify the levels of lipidemia in the diabetic patients in our area. Methods: This study was conducted on 100 diabetic and 100 healthy patients, with 50 patients were males and 50 were females in both groups. Blood was collected in sodium fluoride tubes for all the patients for the estimation of glucose (both fasting and post prandial) and in serum tubes for lipids such as Triglycerides, Total cholesterol, High density cholesterol, Low density cholesterol and Very low density cholesterol. Results: The total cholesterol among the males who were diabetic was in the normal range in 46% and high in 20% of the patients. Among the control, i.e. non diabetic patients, 76% of them had total cholesterol in the normal range and high cholesterol levels were observed in only 8% of them. The levels of triglycerides, total cholesterol and LDL were significantly higher in the patients with diabetes, compared to the non diabetic patients. HDL in these patients was significantly low. Conclusions: The incidence of raised lipid levels in the diabetic patients is very high and since the elevated levels of lipids especially in these patients can lead to CHD and its complications, it is important for the monitoring of these levels throughout the course of the disease.